Effectiveness of cryotherapy and nervous transcutaneous electro stimulation in sportsmen with affections of the osteomyoarticular system - Adrian González Méndez; Niraida Márquez del Pozo; Yesneris Baracaldo Lizano; Carmen María Pérez Flores; Lidellis Afonso Felipe (Centro Provincial de Información de Ciencias Médicas, 2022)
Introduction: The serious trauma constitutes one of the main causes of death and disability. Although it is a very heterogeneous disease as for its origin, types of injure and seriousness, great uncertainty exists as for its prognosis.   Objective: To evaluate the effectiveness of cryotherapy and the nervous transcutaneous electroestimulation for the decrease of pain and edema in sportsmen with affections of the osteomyoarticular system.  Methods: An observational, descriptive and retrospective study of 5548 sportsmen with affections of the osteomyoarticular system was carried out, they went to the Physical Rehabilitation Service of the José Antonio Huelga Stadium in Sancti Spíritus, between November, 2018 and December, 2019, to receive cryotherapy and nervous transcutaneous electroestimulation for the decrease of edema and pain. Among the studied variables figured: sex, age, type of sport that they practiced, injure that presented recovery and time of disappearance of symptoms. Results: There was a prevalence of the male sex (66.83 %), the 18-21 age group (57.33 %), football and athletics as sports with a higher number of affected patients (23.08 and 22.85 %, respectively), as well as sprains (56.54 %) and fractures (20.81%) as main lesions.    Conclusions: The applied therapy was effective and safe to diminish the edema and pain in sportsmen due to traumatic diseaes of the osteomyoarticular system.